ANALISIS KEBUTUHAN PENGEMBANGAN SUMBER DAYA MANUSIA SETELAH PENERAPAN SMM ISO 9001 : 2008 DI BALAI KARANTINA PERTANIAN KELAS I MATARAM - I Putu Terunanegara (Master of Management, Mataram University, 2017)
This research is aimed at determining and analysing the differences of performance of agricultural quarantine class I Mataram before and after the implementation of Quality Management System (SMM) ISO 9001:2008 as well as analysing the need of human resource development after the implementation of Quality Management System (SMM) ISO 9001:2008. This research is descriptive study with quantitative approach supported by qualitative data. The quantitative analysis was conducted with Anova analysis and Force Field Analysis (FFA) or the field strength while the qualitative data were collected through in-depth interview and FGD. The research showed that there is significant differences between the performance of agricultural quarantine class I Mataram before and after the implementation Quality Management System (SMM) ISO 9001:2008. The critical issues of this research is the limited functional technical and general staffs, the quality and competency of human resource did not meet the standard of service needed, the lack of staffs’ commitment in serving the public, the limited facilities of service, and the indiscipline staffs in applying the standard operational procedure. The strategic issued in this research are the low quality of service, certification of the quarantine in the agricultural quarantine class I Mataram. The need assessment of human resource development after the implementation of SMM ISO 9001:2008 is non-apparatus development (N-ED) through dissemination of quarantine to stakeholder and training for apparatus (ET) through training on the ethics of service, the use of service application ware and laboratory apprenticeship. Keywords: performance, Quality Management System (SMM) ISO 9001:2008, Anova, FFA, critical issues, strategic issues, human resource development, agricultural quarantine.